PERANCANGAN MEDIA INTERAKTIF BERBASIS ANIMASI 2D UNTUK PENGENALAN HURUF ALFABET DAN ANGKA PADAANAK DI RA PERWANIDA 01 CEPIRING - Devi Sartika; Bagus Sudirman; Ahmad Ashifuddin Aqham; Edy Siswanto; Dendy Kurniawan (LPPM Politeknik Pratama Kendal, 2026)
Learning while playing is the most enjoyable way for children to understand something new. Based on this idea, this study designed an interactive 2D animation-based learning media entitled “LANCAR”, as an effort to provide a more interesting and interactive learning experience for early childhood. The background of this research stems from the learning conditions at RA Perwanida 01 Cepiring, which still uses conventional media, thus necessitating the application of digital media to support the learning process. This research uses the R&D (Research and Development) method with the MDLC (Multimedia Development Life Cycle) development model, which consists of six stages, namely concept, design, material collection, development, testing, and distribution. The development was carried out using Adobe Animate CC 2023 with child-friendly visual designs, sounds, and animations. The test results showed that the media was very suitable for use, with an average of 92.5% from subject matter experts, 90% from media experts, and 88.9% from user trials. In conclusion, this 2D animation-based interactive learning media is feasible and effective for introducing letters and numbers.